Ferulic Acid Improves Functional Recovery after Acute Spinal Cord Injury in Rats by Inducing Hypoxia to Inhibit microRNA-590 and Elevate Vascular Endothelial Growth Factor Expressions - Li, Zhenjie; Wang, Shengyun; Li, Wenfang; Yuan, Hongbin (Frontiers in Molecular Neuroscience, 2017)
Spinal cord injury (SCI) is the leading cause of paralysis, disability and even death in severe cases, and neural stem cells (NSCs) transplant has been employed for repairing SCI. Ferulic acid (FA) is able to promote neurogenesis in various stem cell therapies. We aimed to investigate the effect of FA on NSC transplant therapy, and the underlying mechanism, in improving functional recovery in SCI rat model. A rat model of SCI was established, which then received transplant of NSCs with or without FA pre-treatment. Functional recovery of the SCI rats was then evaluated, in terms of spinal cord water content, myeloperoxidase activity and behavioral assessments. Effect of FA in inducing hypoxia in NSCs was also assessed, followed by identifying the hypoxic regulated microRNA and the subsequent target gene. Transplant of FA pre-treated NSCs improved functional recovery of SCI rats to a more significant extent than NSCs without FA pre-treatment. The beneficial effects of FA in repairing SCI was mediated by inducing hypoxia in NSCs, which in turn inhibited microRNA-590 to elevate vascular endothelial growth factor expression. Our findings support the clinical potential of FA in improving efficacy of NSC transplant therapy for treatment of SCI.